2021
DOI: 10.3390/jcm10081661
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Platelet Glycoside Residues in the Haemostasis of Patients with Immune Thrombocytopaenia

Abstract: Loss of sialic acid from the carbohydrate side chains of platelet glycoproteins can affect platelet clearance, a proposed mechanism involved in the etiopathogenesis of immune thrombocytopaenia (ITP). We aimed to assess whether changes in platelet glycosylation in patients with ITP affected platelet counts, function, and apoptosis. This observational, prospective, and transversal study included 82 patients with chronic primary ITP and 115 healthy controls. We measured platelet activation markers and assayed pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…They showed that megakaryopoiesis, platelet apoptosis and platelet desialylation did not follow a specific pattern in ITP patients. A recent study showed that changes in glycoside composition of glycoproteins on the platelets’ surface impaired the functional capacity of platelets and increased their apoptosis, which may be related to ITP severity ( 55 ). Our data showed that half of the samples (50%) exhibited both abnormalities; 24% and 16% of these samples presented only increased apoptosis or desialylation, respectively; while 10% of them behaved normally.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that megakaryopoiesis, platelet apoptosis and platelet desialylation did not follow a specific pattern in ITP patients. A recent study showed that changes in glycoside composition of glycoproteins on the platelets’ surface impaired the functional capacity of platelets and increased their apoptosis, which may be related to ITP severity ( 55 ). Our data showed that half of the samples (50%) exhibited both abnormalities; 24% and 16% of these samples presented only increased apoptosis or desialylation, respectively; while 10% of them behaved normally.…”
Section: Discussionmentioning
confidence: 99%
“…35 Apart from the importance of sialic acid in the platelet clearance, 117 more researchers also found that sialic acid played an important role in the production, functional capacity, and apoptosis of platelets. 118,119 At the same time, non-responders to the first-line therapies had significantly higher levels of platelet desialylation. 120 More studies are needed to further establish the importance of platelet desialylation in ITP.…”
Section: Sialic Acidmentioning
confidence: 97%
“…RCA-I and ECL preferentially bind to glycans terminating in Gal or GalNAc, the monosaccharides expected to be exposed following cleavage of Sia. In several flow cytometry studies, ITP platelets were shown to have increased binding to RCA-I and/or ECL compared with healthy platelets, suggesting desialylation of platelet glycans [27–31].…”
Section: Sialic Acid In Immune Thrombocytopenia Pathophysiologymentioning
confidence: 99%